PENGABDIAN KEPADA MASYARAKAT PENINGKATAN ATAP MUSHOLLA AL KHOIRIYAH - Pradiptiya, Andikanoza (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Jakarta, 2020)
Al Khoiriyah Mosque is one of the Muslim prayer facilities in the neighborhood of Rt.05 /Rw.09, Kp.Lio, Bojong Village Pondok Terong, Cipayung Jaya District, Depok. The mosque is used mainly when praying tarawih during Ramadan. DIV Teknik Konstruksi Gedung Community Service Activities for the DIV Teknik Konstruksi gedung Study Program include upgrading and repairing toilet roofs, ablutions, sloof walls, and ceilings. The work of upgrading and repairing is expected to provide adequate mosque infrastructure to increase piety and faith in God Almighty in the location in question. The specific target of this activity is to improve the physical condition of the mosque in Rt.05 / Rw.09, Kp.Lio, Bojong Village Pondok Terong, Cipayung Jaya District, Depok. The method used to achieve the above objectives involves the collaboration of the Community Service Study Team of the DIV Teknik Konstruksi Gedung, Civil Engineering Department, Jakarta State Polytechnic with residents working together to repair the mosque. This activity is completed within 2 months.